Smooth muscle cell Piezo1 depletion results in impaired contractile properties in murine small bowel - Geoanna M. Bautista; Yingjie Du; Michael J. Matthews; Allison M. Flores; Nicole R. Kushnir; Nicolle K. Sweeney; Nam Phuong N. Nguyen; Elmira Tokhtaeva; R. S. Solorzano-Vargas; Michael Lewis; Matthias Stelzner; Ximin He; et al. (Communications Biology)
Abstract Piezo1 is a mechanosensitive cation channel expressed in intestinal muscularis cells (IMCs), including smooth muscle cells (SMCs), interstitial cells of Cajal, and Pdgfrα+ cells, which form the SIP syncytium, crucial for GI contractility. Here, we investigate the effects of SMC-specific Piezo1 deletion on small bowel function. Piezo1 depletion results in weight loss, delayed GI transit, muscularis thinning, and decreased SMCs. Ex vivo analyses demonstrated impaired contractile strength and tone, while in vitro studies using IMC co-cultures show dysrhythmic Ca2+ flux with decreased frequency. Imaging reveal that Piezo1 localizes intracellularly, thereby likely impacting Ca2+ signaling mechanisms modulated by Ca2 + -handling channels located on the sarcoplasmic reticulum and plasma membrane. Our findings suggest that Piezo1 in small bowel SMCs contributes to contractility by maintaining intracellular Ca2+ activity and subsequent signaling within the SIP syncytium. These findings provide new insights into the complex role of Piezo1 in small bowel SMCs and its implications for GI motility.